ANALISIS PERBANDINGAN RASIO RESIKO PERBANKAN SEBELUM DAN SESUDAH GO PUBLIC - Dikdik Megantara (LPPM POLITEKNIK LP3I BANDUNG, 2016)
ABSTRACT : This research is intended to reveal how far risk ratios before and after go public and if there are any significant difference in banking risk ratios before and after go public. This research was conducted at Bursa Efek Jakarta, which the research objects are banking risk ratios from the bank that goes public at the beginning of 1994. The research method used in this research is comparative method which data were collected from field research and library research. The hypothesis is tested by comparative methods which data were collected from field research and library research. The hypothesis is tested by comparative hypothesis testing with using T distribution. The level of significance used in this research was 5%. Based on the result, writer conclude that there is no significant difference of liquidity risk ratio before and after go public, showing by t-count < t (1- α) namely -1,75525 < 2,228. There is no significant difference of credit risk ratio before and after go public, showing by t-count < t (1- α) namely -0,417093 < 2,228. There is no significant difference of asset risk ratio before and after go public, showing by t-count < t(1- α) namely -1,082841 < 2,228. There is no significant difference of saving risk ratio before and after go public, showing by t-count < t (1-α) namely -1,093752 < 2,228. Generally, based on statistical testing, there is no significant difference of banking risk ratio before and after go public, showing by t-count < t (1- α) namely 1-285141 < 2,228.